URANIUM DEPOSITS OF THE EL'KON ORE DISTRICT IN THE ALDAN SHIELD - Miguta A.K. (My University, 2001)
The paper presents the characteristics of the main uranium deposits of the El'kon ore district in the Aldan Shield, which is regarded as the primary reserve of uranium resources in Russia. The deposits are localized in ore-bearing structures of four types: (1) rejuvenated ancient regional faults, (2) large Mesozoic zones partly inheriting ancient structural elements, (3) exocontacts of preore Mesozoic dikes, and (4) variously oriented Mesozoic fracture zones. Around 80% of uranium resources are confined to rejuvenated ancient faults. In the major Yuzhnaya zone, the ore mineralization was traced for nearly 25 km along strike and for more than 2 km along dip without reaching its lower limit. These parameters are unique for hydrothermal deposits of uranium and other metals. Different types of uranium-bearing zones vary in geological structures, combination of tectonic elements of different ages, morphology of ore bodies and their vertical extent. At the same time, mineral associations of uranium ores reveal no considerable lateral changes or vertical zoning. Uranium ores are closely related to pyrite-carbonate-K-feldspar metasomatites, which are rich in K2O, CO2, and sulfide sulfur and contain an Au admixture of a few g/t. In the northwestern sector of the ore district, the primary brannerite ores were transformed into uraninite ores during the emplacement of postore Mesozoic alkaline intrusions. There are no analogs to the El'kon uranium deposits in the world. To a certain degree, they resemble some fault-related deposits in sodic metasomatites of the Ukrainian Shield. The latter, however, were formed during the Early Proterozoic protoactivization and granitization. In central Aldan, uranium deposits originated during the Mesozoic tectonomagmatic activization and are 1.5 Ga younger than the crystalline basement and ancient faults. These factors define the specific features of the deposits.
Keywords: Proterozoic; Mesozoic; Mesozoic; Precambrian::Proterozoic; Докембрий::Протерозой; Мезозой